Peningkatan Kualitas Pembelajaran Pendidikan Agama Islam di SMP Ma’arif NU 2 Kemranjen Tahun Pelajaran 2017/2018 - Miftahur Rahman; Maryatun Kiptiyah (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
The quality of learning is something that needs to be improved along with the times. Islamic religious education is a conscious effort that takes place in human life to meet their needs through guidance, teaching, and or training in making quality human beings so they can achieve happiness in the world and the hereafter. Islamic Religious Education Teachers are one of the parties who play a role and are responsible for improving the quality of PAI learning. Thus it is necessary to conduct research on how the efforts of PAI teachers in improving the quality of PAI learning. This study aims to find out how PAI teachers improve the quality of PAI. The results showed that the efforts of Islamic religious education teachers in improving the quality of PAI learning through teaching and learning activities in the classroom and outside the classroom, carried out by learning planning, using learning methods and media to the maximum and evaluation, the existence of a zero-hour program, the existence of study groups and activities extracurricular in the form of tawah, tartil and hadroh. Outside the classroom, it is carried out through PHBI, boarding schools express and pilgrimage. Supporting factors are the majority of teachers who are graduates of Islamic boarding schools, a conducive and religious school environment and the fabric of cooperation between schools, parents and the community. Constraints faced are, there is a minority of students who live outside the boarding school, so that it lags in PAI learning materials. The improvement in the quality of PAI learning has been successful, as seen from the average value of PAI obtained by students every year that is constantly increasing.